MODEL PENDIDIKAN KARAKTER DENGAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA PENDIDIKAN ANAK USIA DINI INKLUSIF DI SEKOLAH ALAM RAMADHANI - Mahwaniya, Indri; Sutarto, Joko; Suminar, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract This research is motivated by the phenomenon of demoralization of the nation's generation which occurs due to the low level of moral understanding that has not been obtained since early childhood and the decreasing intensity of Pancasila values ​​in PAUD institutions. This study aims to determine the implementation of the character education model in inclusive PAUD at Alam Ramadhani School. The research method uses a qualitative research approach with a single case study. Data collection techniques using observation and structured interviews. The results of the research show that the implementation of the inclusive PAUD character education model at Alam Ramadhani School is oriented towards strengthening the profile of Pancasila students (P5) including six dimensions, namely religious values, diversity, mutual cooperation, independence, creativity and innovation with learning activities referring to project-based activities starting from from introduction, contextualization, planning, action and reflection aimed at capacity building for early childhood. Where in practice P5 activities use nature as a medium and learning resource by directly involving all students including ABK. Keywords: Character Education Model, P5, Inclusive PAUD